Carbon price dynamics: Evidence from Phase II of the European Emission Trading Scheme - Wilfried Rickels; Dennis Görlich; Gerrit Oberst; Sonja Peterson (Kiel Institute for the World Economy (IfW), 2012)
In this paper we empirically investigate potential determinants of allowance (EUA) price dynamics in the European Union Emission Trading Scheme (EU ETS) during Phase II. In contrast to previous papers, we analyze a significantly longer time series, place particular emphasis on the importance of price variable selection, and include an extensive data of renewable energy feed-in in Europe. We show (i) that results are extremely sensitive to choosing different price series of potential determinants, such as coal and gas prices, (ii) that EUA price dynamics are only marginally influenced by renewable energy provision in Europe, and iii) that EUA prices currently do not reflect marginal abatement costs across Europe. We conclude that the expectation of a more mature allowance market in Phase II cannot be confirmed.
Keywords: C22; G14; Q54; 330; Carbon emission trading; EU ETS; Carbon price influence factors; Fuel switching